Analisis Strategi Pemasaran UMKM Martabak Tip Top - Santi Rimadias; Fahru Zaman; Keisha Aulia Zahra; Suci Wulan Ramadhani Basumbul; Azzahra Syahirra; Yan Martawijaya (Global Leadership Organizational Research in Management, 2025)
This study presents an analysis of the marketing strategies of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, which are the backbone of the national economy. Using qualitative and quantitative approaches, this study aims to identify the challenges and opportunities faced by MSMEs, as well as their impact on local economic growth. The subject of the research in this case is the Martabak Tip Top MSMEs. Data was collected through surveys, interviews, and relevant literature studies. The results of the analysis show that Martabak Tip Top MSMEs face various obstacles in their marketing strategy, such as digitalization and increasing consumer awareness of local products. This research is expected to provide strategic recommendations for stakeholders to support the development of MSMEs, so that they can contribute more to the national economy and job creation.